If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2z + 3 + -4z = 3z + -7 Reorder the terms: 3 + 2z + -4z = 3z + -7 Combine like terms: 2z + -4z = -2z 3 + -2z = 3z + -7 Reorder the terms: 3 + -2z = -7 + 3z Solving 3 + -2z = -7 + 3z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-3z' to each side of the equation. 3 + -2z + -3z = -7 + 3z + -3z Combine like terms: -2z + -3z = -5z 3 + -5z = -7 + 3z + -3z Combine like terms: 3z + -3z = 0 3 + -5z = -7 + 0 3 + -5z = -7 Add '-3' to each side of the equation. 3 + -3 + -5z = -7 + -3 Combine like terms: 3 + -3 = 0 0 + -5z = -7 + -3 -5z = -7 + -3 Combine like terms: -7 + -3 = -10 -5z = -10 Divide each side by '-5'. z = 2 Simplifying z = 2
| 9w+w= | | 8-4x=-6 | | 3(x+7)=26 | | 55=39-5c | | 4x(3x-1)= | | 3(5c-1)=4(3c+2) | | 4v^2=-11v-6 | | 6n-2=4n+6 | | 3x(x+5)= | | 2x^2-20x=-42 | | y+5+2y= | | 6x+5x=63 | | 4(n-1)=-8 | | y^2+9y=-20 | | 5y-2(y+4)=1 | | 3x^2-8x^7-2x^2=9x^7 | | 6x^2-8x-12=0 | | 2K(K+3)=-9 | | 2K(K+3)=9 | | 3(x-4)+15=2(x+3) | | 6y^2-6=0 | | 5/12-7/8= | | 4x^2=4x | | -1/5-4(m+1/12)=39/10(m-11/6) | | a^2b^2-121=0 | | 9+-10x+x^4=0 | | x+6x-40=0 | | -10x+3+9x=-x-7 | | x^4-10x+9=0 | | 5v^3-65v^2+200v=0 | | 2x-7/3=-7 | | 8a+a= |